Strengthening Emotional Intelligence through Pranatacara and Pamedarsabda Training for the Srikandi Women Farmers Group in Karangmalang, Mijen, Semarang: Strengthening Emotional Intelligence through Pranatacara and Pamedarsabda Training for the Srikandi Women Farmers Group in Karangmalang, Mijen, Semarang - Algifahmy, Ayu Faiza; Fahrurrozi, Fahrurrozi; Lailatul Mukarromah, Warda Rida; Septianingrum, Hilma (Institut Riset dan Publikasi Indonesia, 2026)
This community service program aims to implement traditional da’wah media as a model for strengthening emotional intelligence among the Srikandi Women Farmers Group in Karangmalang through pranatacara and pamedarsabda. The program was motivated by the strategic role of mothers as primary educators within the family and the need to strengthen emotional capacities relevant to the socio-cultural context of rural communities. This study employed a Participatory Action Research (PAR) approach involving 35 participants. The program included theoretical sessions, pranatacara and pamedarsabda training, as well as practical application within family settings. Data were collected through observation, interviews, and documentation, and were analyzed descriptively using a qualitative approach. The results showed that most participants experienced an increased understanding of the functions of pranatacara and pamedarsabda as media for family da’wah and emotional communication. Based on observational findings, participants began to use Javanese language in a more polite, structured, and persuasive manner during communication practices. In addition, participants who initially lacked confidence gradually demonstrated greater courage in public speaking and improved ability to manage nervousness during practice sessions. Reflection results also indicated that the training helped participants become more patient, more careful in choosing words, and better able to control their emotions when communicating with family members. These findings indicate that traditional da’wah media rooted in local culture can serve as a means of strengthening emotional intelligence and interpersonal communication among rural women. .